(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2026)
This research, conducted in 2024, aimed to investigate the efficacy of the local isolate N19 of Beauveria bassiana (Bals.) Vuil., to colonize tomato plants, promote their growth, and protect them from infection with the root- knot nematode Meloidogyne spp. Göldi under laboratory conditions. The ability of the fungal isolate to colonize tomato leaves, stems and roots was evaluated two months after the experiment. Plant height and fresh weight of shoots and roots were measured. Galls and egg masses formed by nematodes on the roots were also counted. The results showed that the isolate N19 was able to colonize tomato stems, leaves, and roots in the laboratory by a percentage up to 50%. However, inoculation of tomato plants with B. bassiana did not enhance the plant growth, nor reduce the number of root-knot nematode galls, egg masses, and galling index compared to the control infected with nematodes only.